Perception of Acceptance of Accounting Information TechnologyOn the Quality of Financial Reports with the Technology Acceptance Model Theory Approach - Nur Azizah -; Siti Mariani Basanang (Faculty of Business and Economics , Universitas Yapis Papua, 2024)
This study uses the Technology Acceptance Model (TAM) approach to examine how perceived usefulness and ease of use of information technology affect the quality of financial reports in hotel businesses in Jayapura City. Data from 101 individuals were collected, and multiple linear regression analysis was used for analysis. With values of 0.005 and <0.001 (p<0.05), the findings indicate that perceived ease of use (X1) and usefulness of technology (X2) significantly affect the quality of financial reports (Y). These two factors explain 81.9% of the variance in the quality of financial reports, based on the coefficient of determination (R2) of 0.819. The importance of using accounting information technology to improve the effectiveness and transparency of financial reporting is the main topic in this study.